Validity and reproducibility of a food frequency questionnaire for adults of São Paulo, Brazil - Soraya Sant'Ana de Castro Selem; Aline Martins de Carvalho; Eliseu Verly-Junior; Jackeline Venâncio Carlos; Juliana Araujo Teixeira; Dirce Maria Lobo Marchioni; Regina Mara Fisberg (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2014)
OBJECTIVES: To assess the validity and reproducibility of a food frequency questionnaire developed for estimating the food consumption of adults in São Paulo, Brazil, based population study. METHODS: A sample of individuals aged above 20 years, of both genders, living in São Paulo, was used for the validation study (n = 77) and reproducibility study (n = 74) of the food frequency questionnaire. To verify the validity and reproducibility of energy and 19 nutrients were applied two food frequency questionnaires (60 items) and three 24-hour dietary recalls (24HR - reference method). The validity was verified by Spearman correlation coefficient (crude and de-attenuated) and weighted Kappa, and reproducibility by intraclass correlation coefficients and weighted kappa. RESULTS: In analyzes of validity de-attenuated correlation coefficients ranged from 0.21 (carbohydrate) to 0.74 (energy), and weighted kappa exceeded 0.40 for 30% of the nutrients. Polyunsaturated fat and folate did not show significant correlation and weighted kappa. In reproducibility correlation coefficients ranged from 0.36 (polyunsaturated fat) to 0.69 (calcium), and weighted kappa exceeded 0.40 for 80% of the nutrients. CONCLUSION: The food frequency questionnaire analyzed has good validity and reproducibility for estimating the food consumption of adults in São Paulo compared to the reference method, so it is an appropriate instrument to be used in epidemiological studies on similar populations. Estimates of polyunsaturated fat and folate should be interpreted with caution.